SOME WAYS OF TEACHING SPEAKING TO ELEMENTARY LEVEL LEARNERS - Bekbergenova Gulayim Ayjarikovna; Tolibaeva Kamila Timurovna (TADQIQOTLAR, 2026)
Abstract: Teaching speaking to elementary level learners is a foundational task in any English language curriculum. At this stage, learners are just beginning to communicate using simple sentences, basic vocabulary, and everyday expressions. Therefore, the main goals are to develop their confidence, help them use language in meaningful contexts, and lay the groundwork for more advanced communication in the future. One of the key principles in teaching speaking to beginners is the necessity of creating a safe, supportive, and motivating classroom environment. Learners at the elementary level are often hesitant to speak for fear of making mistakes. Encouraging positive attitudes towards mistakes as part of the learning process is essential. Teachers should praise attempts to speak, provide constructive feedback, and foster a classroom culture in which every student feels comfortable expressing themselves regardless of their proficiency.